2019
DOI: 10.1186/s13046-019-1217-9
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant activation of CYR61 enhancers in colorectal cancer development

Abstract: Background High expression of secreted matricellular protein cysteine-rich 61 ( CYR61 ) correlates with poor prognosis in colorectal cancer (CRC). Aberrant enhancer activation has been shown to correlate with expression of key genes involved in cancer progression. However, such mechanisms in CYR61 transcription regulation remain unexplored. Methods Expression of CYR61 was determined by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…In our results, both Cyr61 in astrocytes and Sgk3 in oligodendrocytes are overexpressed and these genes could be potential therapeutic targets in this phase. Despite the lack of research on ischemic stroke, previous studies have suggested that the Cyr61 gene is closely associated with the proliferation of stressed and tumoral cells ( Schwarz et al, 2002 ; Xie et al, 2019 ; Sun et al, 2020 ). Overexpression of the Cyr61 gene may help astrocytes survive under acute ischemic stroke conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, both Cyr61 in astrocytes and Sgk3 in oligodendrocytes are overexpressed and these genes could be potential therapeutic targets in this phase. Despite the lack of research on ischemic stroke, previous studies have suggested that the Cyr61 gene is closely associated with the proliferation of stressed and tumoral cells ( Schwarz et al, 2002 ; Xie et al, 2019 ; Sun et al, 2020 ). Overexpression of the Cyr61 gene may help astrocytes survive under acute ischemic stroke conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cyr61/CNN1 has been described as potential serum marker for CRC (Song et al, 2017), whereas Cyr61 expression in the tumor tissue indicates poor prognosis in colon cancer patients being statistically associated with greater mortality (Jeong et al, 2014). Altered activation of CYR61 gene enhancers occurs during CRC development, being CYR61 expression induced by FOXA1 and CBP in colon cancer cells pointing at both transcription factors as targets for CRC treatment (Xie et al, 2019). Interestingly, PGF2a through FP receptors can upregulate the expression of CYR61 mRNA (Xu et al, 2009).…”
Section: Cox-2 and The Tgf-b Pathwaymentioning
confidence: 99%
“…We recently characterized CYR61 enhancers that play important roles in promoting cell migration during colon cancer progression [25]. In this study, to better understand enhancer regulation in cancer, we show the epigenetic co-regulation of TMPRSS2 and PRCAT38 via eRNA transcription, enhancer-promoter interaction, and gene regulation by transcription factors, revealing a co-regulatory function of two enhancers, denoted by E1 and E2 in the transcription of PRCAT38 and TMPRSS2 .…”
Section: Introductionmentioning
confidence: 73%